EDGE: from quiescent to gas-rich to star-forming low-mass dwarf galaxies. Issue 2 (12th August 2020) - Rey, Martin P; Pontzen, Andrew; Agertz, Oscar; Orkney, Matthew D A; Read, Justin I; Rosdahl, Joakim
ABSTRACT: We study how star formation is regulated in low-mass field dwarf galaxies ($10^5 \le M_{\star } \le 10^6 \, M_\mathrm{\odot }$ ), using cosmological high-resolution ($3 \, pc$ ) hydrodynamical simulations. Cosmic reionization quenches star formation in all our simulated dwarfs, but three galaxies with final dynamical masses of $3 × 10^{9} \, M_\mathrm{\odot }$ are subsequently able to replenish their interstellar medium by slowly accreting gas. Two of these galaxies reignite and sustain star formation until the present day at an average rate of $10^{-5} \, M_\mathrm{\odot } \, \text{yr}^{-1}$, highly reminiscent of observed low-mass star-forming dwarf irregulars such as Leo T. The resumption of star formation is delayed by several billion years due to residual feedback from stellar winds and Type Ia supernovae; even at z = 0, the third galaxy remains in a temporary equilibrium with a large gas content but without any ongoing star formation. Using the 'genetic modification' approach, we create an alternative mass growth history for this gas-rich quiescent dwarf and show how a small $(0.2\, dex)$ increase in dynamical mass can overcome residual stellar feedback, reigniting star formation. The interaction between feedback and mass build-up produces a diversity in the stellar ages and gas content of low-mass dwarfs, which will be probed by combining next-generation H i and imaging surveys.